The Quality of Growth: Macroeconomics Causality on Growth in Indonesia - Chinta Khusnia; Indah Yuliana; Nihayatu Aslamtis Solekah; Yusuf Falaqi Ahmad; Talia Putri Kamila (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to analyze the impact of inflation, the interest rate (BI rate), and the exchange rate on economic growth in Indonesia from 2016–2023. The data used were obtained from the official websites of the World Bank, the International Monetary Fund, and the Central Statistics Agency, and were analyzed using multiple linear regression with the assistance of Eviews 10 software. The results of the study show that inflation has a significant negative impact on economic growth in Indonesia. Conversely, the BI interest rate and the exchange rate variables do not show a substantial effect on economic growth during the period studied. These findings emphasize the importance of controlling inflation as a primary policy to support sustainable economic growth.